Hydrothermal Preparation and High Electrochemical Performance of NiS Nanospheres as Anode for Lithium-Ion Batteries - Wang, Lin-Hui; Ren, Long-Long; Qin, Yu-Feng; Li, Qiang (Frontiers in Chemistry, 2022)
Nickel sulfide has been widely studied as an anode material for lithium-ion batteries on account of its environment friendliness, low cost, high conductivity, and high theoretical capacity. A simple hydrothermal method was used to prepare NiS nanospheres materials with the size in the range of 100 nm-500 nm. The NiS nanospheres electrodes exhibited a high reversible capacity of 1402.3 mAh g-1 at 200 mA g-1 after 280 cycles and a strong rate capability of 814.8 mAh g-1 at 0.8 A g-1 and 1130.5 mAh g-1 when back to 0.1 A g-1. Excellent electrochemical properties and the simple preparation method of the NiS nanospheres make it possible to prepare NiS on a large scale as the anode of lithium-ion batteries.